Do's and don'ts of R&D Benchmarking - Ransley, Derek L.
Derek L. Ransley presents guidelines for getting the most out of your benchmarking activity.
Make the most of your benchmarking effort by following these guidelines.
When it is accepted that R&D is a process, then the notion of a continuous need to improve becomes apparent. Benchmarking is a quality tool that can be used to learn from better performers how to improve. Experience has shown that there are some activities that enhance the quality of benchmarking (Do's). There are other things to avoid (Don'ts) in order to keep out of trouble. The Do's and Don'ts can be used as checklists to help you make the most of your benchmarking efforts. It is even more convenient to map the lists into the different stages of a generic benchmarking model. The Do's and Don't then become part of a working document.
Keywords: R&D benchmarking